The impact of a teacher's pedagogical skills and the classroom environment on students’ academic achievements is mediated by their motivation to learn in the field of economics - Khoiriyah, Bait Anti; Waspada , Ikaputera; Kurjono, Kurjono (Gema Wiralodra, 2023)
The purpose of this study was to obtain information about the effect of teacher pedagogical competence and learning climate on learning outcomes by mediating learning motivation. This study uses a quantitative approach to the explanatory survey method with data collection techniques through questionnaires. The population of this study was 960 students of class XI Social Sciences at Bandung City Public High School in the Southeast Region. Using random sampling and proportional random sampling techniques, a sample of 241 students was obtained. The data analysis method used is descriptive statistical analysis and path analysis. The study results show that (a) teacher pedagogic competence, learning climate, learning motivation, and learning outcomes are in the medium category. (b) A teacher's pedagogical competence does not affect learning motivation. (c) Learning climate has a positive effect on learning motivation. (d) teacher's pedagogical competence does not affect learning outcomes. (e) Learning climate has a positive effect on learning outcomes. (vi) learning motivation has a positive effect on learning outcomes. (f) Learning motivation does not mediate the effect of teacher pedagogical competence on learning outcomes. (g) Learning motivation mediates the effect of learning climate on learning outcomes.